2010
DOI: 10.1016/j.physb.2010.01.115
|View full text |Cite
|
Sign up to set email alerts
|

Searching for crystallographic superstructures in -(BEDT-TTF)2Cu[N(CN)2]Br

Abstract: To resolve a superstructure formation previously reported for the organic superconductor κ-(BEDT-TTF) 2 Cu[N(CN) 2 ]Br, we present synchrotron x-ray diffraction experiments carried out at the MAGS beamline at BESSY, HZB. Surprisingly, in our low temperature (28K) experiments, when searching kspace at (h 0 3.5), h = 7, 8 and (h 0 0.5), h = 5, 7, for none of these spots we could detect scattering intensity associated to a superstructure formation, in contradiction to previous reports. Our data suggest that detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It should be noted that the origin of the glasslike transition in the mentioned systems [31] is still controversial. Recent synchrotron x-ray diffraction experiments [33,48] established the level of residual ethylene group disorder in -Br. From this the authors concluded that the glasslike transition is not primarily caused by the configurational freezing-out of the ET-endgroup motions, but rather other structural and electronic degrees of freedom have to be taken into account.…”
Section: B Thermal Expansionmentioning
confidence: 99%
“…It should be noted that the origin of the glasslike transition in the mentioned systems [31] is still controversial. Recent synchrotron x-ray diffraction experiments [33,48] established the level of residual ethylene group disorder in -Br. From this the authors concluded that the glasslike transition is not primarily caused by the configurational freezing-out of the ET-endgroup motions, but rather other structural and electronic degrees of freedom have to be taken into account.…”
Section: B Thermal Expansionmentioning
confidence: 99%